An Examination of the Moderate Ijtihad Method from the Perspective of Abdullah bin Bayyah and Its Application in the Formulation of Islamic Law - Yaqin, Ainol (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2025)
Fiqh is a product of ijtihad, developed through a dialectical process between textual sources and real-world contexts. Fiqh possesses various characteristics, some of which are rigid and complex, while others are more flexible and adaptable. Rigid fiqh arises from an ijtihad that is fixated on textual understanding without exploring its objectives (maqashid), whereas excessively flexible fiqh is formulated from an ijtihad that prioritises maqashid while disregarding the texts (al-naṣ). Both patterns of ijtihad represent extremes that are not justified within the framework of Islam. Consequently, it is essential to examine and apply a flexible and dynamic fiqh derived from moderate ijtihad. This article aims to analyse and identify applicable concepts related to the theory of moderate ijtihad as articulated by Abdullah bin Bayyah, subsequently implementing these concepts in response to contemporary issues. This research constitutes a literature review that investigates the thoughts of contemporary scholars and analyses them employing a descriptive-analytical approach to derive meaningful insights. This study plays a crucial role in examining and applying the concept of moderate ijtihad to address contemporary matters in Islamic jurisprudence, which continue to evolve alongside the progress and transformation of human civilisation. Furthermore, moderate ijtihad has the potential to produce Islamic legal rulings that are not only flexible and adaptive but also firmly grounded in the higher objectives of sharia (maqashid sharia). The research findings indicate that Abdullah bin Bayyah's method of moderate ijtihad involves linking al-nuṣūṣ with maqashid sharia, observing and distinguishing between al-thawābit and al-mutaghayyirāt, considering the context of changing times in formulating Islamic law, acknowledging customs, ‘urf, or local traditions, contemplating the consequences, and considering conditions, as well as personal and community psychology. The application of moderate ijtihad results in the formulation of legal rulings, such as the prohibition of gelatin derived from pigskin and bones—except in cases of necessity—and the obligation of marriage registration.